METODE URUTAN PARSIAL UNTUK MENYELESAIKAN MASALAH PROGRAM LINIER FUZZY TIDAK PENUH - Jiwangga, Sesar Sukma; Irawanto, Bambang; Djuwandi, Djuwandi (MATEMATIKA, 2017)
Not fully fuzzylinear programming problem have two shapes of objecyive function. that is triangular fuzzy number and trapezoidal fuzzy number. The decision variables and constants right segment only has a triangular fuzzy number. Partial order method can be used to solve not fully fuzzy linear programming problem with decision variables and constants right segment are triangular fuzzy number. The crisp optimal objective function value generated from the partial order method.